Five new species and a new record of the genus Aculops Keifer (Acari: Eriophyidae: Phyllocoptinae) from China - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2007)
Five new species and a new record in the genus Aculops Keifer from China are described and illustrated, namely Aculops baligouis sp. nov. on Acer sp. L. (Aceraceae); Aculops tianchis sp. nov. on Betula sp. L. (Betulaceae); Aculops sienses sp. nov. on Ligustrum siense Lour. (Oleaceae); Aculops salixis sp. nov. on Salix sp. L. (Salicaceae); Aculops yangxianensis sp. nov. on Sophora japonica L. (Leguminosae) and Aculops chinonei Huang, on Rhus chinensis Mill. (Anacardiaceae). A key to the species of Aculops in China is provided.